Perancangan dan Pembuatan Sistem Pengereman Pada Mobil Minimalis Roda Tiga - Farihatul Jannah; Sudiyono Sudiyono; Tri Andi Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
In the modern era, automotive industry is developing rapidly, from motorcycle until car. There is new innovation in automotive industry, it is a minimalist three wheels car. A car has many parts that very complex. One of them that also very important is brake system because it is deal with safety. So it takes the analyze and design of the brake system that according to minimalist three wheels car. In this final project, the author will design a brake system that suitable to minimalist three wheel car. And then have calculating the force that is required by the driver to stop a car. The author designed the brake system using AutoCAD software. Based on data analysis that has been done, the brake system that suitable to minimalist three wheel car are disc brake with hydraulic system for front wheel and drum brake with mechanic system for rear wheel. Based on the design of brake system that have made, the force that the driver needed to stop a car is 559,87 N. Brake’s specification that used to minimalist three wheels car are disc brake with diameter about 220 mm, master silinder’s diameter is 12,7 mm, piston caliper’s diameter is 34 mm and tromol brake’s diameter is 130 mm.